TREATMENT OF ARVI (Modern education and development, 2025)
Every adult suffers from influenza or other acute respiratory viral infections on average 2-4 times a year, a schoolchild - 4-5 times, a preschool child - 6 times, a child of the first year of life has from 2 to 12 episodes of acute respiratory viral infections. The polyetiology of ARVI pathogens and the variability of viruses involved in the epidemic process, complications after an illness, necessitate the search for new diagnostic methods and optimization of treatment and preventive measures.